Physical, morphological and antibacterial properties of lime essential oil nanoemulsions prepared via spontaneous emulsification method - Liew, Sin Neen; Utra, Uthumporn; Alias, Abdul Karim; Tan, Tai Boon; Tan, Chin Ping; Yussof, Nor Shariffa (Elsevier, 2020)
Lime essential oil (EO) nanoemulsions from key lime (Citrus aurantifolia), kaffir lime (Citrus hystrix) and calamansi lime (Citrofortunella microcarpa) were produced by using spontaneous emulsification method and their particle size, polydispersity index (PDI), turbidity, morphology and antibacterial properties were investigated. Lime EO nanoemulsions were produced by mixing 5% (v/v) of oil phase (lime EO and corn oil at the ratio of 8:2) with 15% (v/v) of Tween 80 and 80% (v/v) of deionized water using magnetic stirring at 750 rpm and 25 °C. Key lime EO nanoemulsion showed the smallest particle size (21 nm), lowest PDI value (0.444) and lowest turbidity (99.0% of transmittance) followed by kaffir and calamansi lime. Transmission electron microscopy (TEM) micrographs revealed sphere-shaped oil particles with different particle size. Freshly prepared calamansi lime EO nanoemulsion was the most effective against Escherichia coli, Salmonella spp, and Staphylococcus aureus by exhibiting the largest diameter of inhibition zone (8.34, 7.71, and 9.98 mm, respectively). Key lime EO nanoemulsion showed the lowest reduction in the antibacterial activity after 1 month of storage at room temperature. The lime EO nanoemulsions showed great potential to be incorporated into water-based food products and beverages as flavouring and antimicrobial agents.